Input Subsidy Programs in Sub-Saharan Africa by Thom Jayne - Jayne, Thomas S. (2013)
IFPRI Policy Seminar "Input Subsidy Programs in Developing Countries What Works, What Doesn’t, and Why?" presentation by Professor Thomas Jayne, Michigan State University on 18 April 2013.